2023
DOI: 10.3847/2041-8213/acd777
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations

Abstract: Magnetic fields in galaxies and galaxy clusters are believed to be the result of the amplification of intergalactic seed fields during the formation of large-scale structures in the universe. However, the origin, strength, and morphology of this intergalactic magnetic field (IGMF) remain unknown. Lower limits on (or indirect detection of) the IGMF can be obtained from observations of high-energy gamma rays from distant blazars. Gamma rays interact with the extragalactic background light to produce electron−pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…As already mentioned, we will focus on the effect of the intergalactic magnetic field. From the non-detection of electromagnetic cascades from blazars, it was concluded that the extragalactic space must be filled with an turbulent magnetic field with a strength of B 10 −14 G with a large filling factor [62][63][64], while an upper limit of B 10 −9 G is derived from Faraday rotation measurements [65]. The nature and the production of the extragalactic magnetic field remain however unknown: A large range of magnetic field strengths, spectral index at small k (i.e.…”
Section: Magnetic Field Modelsmentioning
confidence: 99%
“…As already mentioned, we will focus on the effect of the intergalactic magnetic field. From the non-detection of electromagnetic cascades from blazars, it was concluded that the extragalactic space must be filled with an turbulent magnetic field with a strength of B 10 −14 G with a large filling factor [62][63][64], while an upper limit of B 10 −9 G is derived from Faraday rotation measurements [65]. The nature and the production of the extragalactic magnetic field remain however unknown: A large range of magnetic field strengths, spectral index at small k (i.e.…”
Section: Magnetic Field Modelsmentioning
confidence: 99%
“…Recently, the observed Fermi LAT and H.E.S.S. spectra of 1ES 0229+200 were made publicly available (Aharonian et al 2023), 6 which we make use of in the present work.…”
Section: Observations Of 1es 0229+200mentioning
confidence: 99%
“…The absorption of gamma-rays by the EBL can account for the entire spectral softening. Further details on the analysis can be found in Aharonian et al (2023).…”
Section: Observations Of 1es 0229+200mentioning
confidence: 99%
See 2 more Smart Citations